(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This article highlights the importance of peace and stability in the path to development, as well as the forms of stability, their occurrence, the consequences of instability, and how important the UN’s “Sustainable Development Goals” are, as well as our tasks in ensuring stability.